Current development situation and prospects of China-made PLC - Lin Hao; Yang Zhenghou; Huo Yuxian (Dianzi Jishu Yingyong, 2023)
This paper briefly reviewed the history of China-made PLC and presented the domestic market situation of PLC, mainstream products of China-made PLC, PLC standards, and relevant national policies. And the existing gaps between foreign and domestic PLC products were analyzed from some aspects including PLC performance indicators, logic programming software, network protocols, product categories, and standardization. Then this paper tried to propose a solution to develop the China-made PLC, combining the characteristics of PLCs of European, American, and Japanese systems. Led by the key projects in the fields of defense industry and critical infrastructure, the China-made PLC will be developed and used based on the domestic independent software and hardware.